Inovação em educação: museus permeados por tecnologia como inspiração para o ambiente escolar - Padula, Roberto Sanches (2015)
This work aims to identify the educational advantages that the museological ambiance and strategies can bring if put into effect in a hybrid (physical and digital) school context. The objective is to verify the educational advantages that could be provided in a school with an innovative design, inspired by the ambiance, curatorial and pedagogical strategies from museums permeated by technology. The literature about innovation is based on concepts from the Oslo Manual and the Centre for Educational Research and Innovation (OECD 2004; 2010) and from the European Commission s Joint Research Centre (FERRARI; CACHIA; PUNIE, 2009). Studies by Falk and Dierking (2000), Hooper-Greenhill et al (2003), Nascimento (2005), Mandarino (2001), Hein (1995), and Alderoqui (2011) forms the basis for themes about visitors experience and education in museums. Trends in education and museums are based on reports by the New Media Consortium (NMC, 2015), and in libraries and hybrid spaces, on the studies by Bilandzic (2013). The studies by Kowaltowski (2011) and Oblinger (2006) are the basis for school architecture. A primary data research with students who have visited museums complements the material. A questionnaire consisting of closed and open questions about generic learning outcomes has indicated that museums can be considered a complementary educational space, as valid as schools. Mostly due to the interactivity, this result indicates that the museum visitors experience is interesting, amusing and motivating, in a way that schools can hardly achieve. The conclusion is that museums can inspire different types of changes in schools, which are grouped here in the form of a proposal for an innovative school environment, pleasant, flexible, permeated by technology, that values informal education and that enables learning practices differentiated from that that normally take place in traditional classrooms, so to provide gain in the learning process